THE EFFECT OF SOCIAL INFLUENCE AND PRODUCT ATTRIBUTES ON CUSTOMER PURCHASE INTENTION: A STUDY OF SECOND-HAND CLOTHES IN MANADO - Cliff Joy Johanes Kalesaran; Maryam Mangantar; Emilia Margareth Gunawan (Universitas Sam Ratulangi, 2022)
The purpose of this research is to analyze the effect of social influence and product attributes on customer purchase intention of second-hand clothes in Manado. The method used in this research is the quantitative method. This research used is purposive sampling method, and 105 samples were collected by using a questionnaire with a 5 Likert scale that was distributed via social media. The data collected are processed and analyzed using the multiple linear regression method. The result of this research shows that social influence (X1) and product attributes (X2) have a positive and significant effect towards purchase intention (Y) both partially and simultaneously.